Rasistiska brott mot utsatta grupper - Therese Enarsson; Karin Åström (Nordisk Tidsskrift for Kriminalvidenskab)
AbstractThis article takes its starting point in Sami and Roma exposure to racism by studying preconditions within the criminal law for dealing with racism against individual victims of crime. The purpose is to identify whether and how individual victims can obtain remedy andreparation when exposed to racism. In this article, that means that the racist act must be criminalized, that the criminal interest of criminalization is the individual victim, and that the racist nature of the crime has legal implications for classification, sentencing and punishment. Methodologically, the study focuses on identifying possible challenges in the application of so-called hate crimes legislation. Two challenges to the application of indivi dual remedies and reparations were identified. First is the difficulty in identifying and establishing (racist) motive. Second is the lack of clear statements from the courts about how assessments have been made in the use of aggravating and mitigating circumstances in sentencing, and if or how they have affected sentencing and punishment. The results of this study show that the legal conditions for individual victims to obtain criminal justice when they have been subjected to racism are insufficient. Problems are primarily due to deficiencies in the formulation of the legislation, but are also seen in its application. Despite a strong contemporary political focus on work to combat racism, no legal changes have been proposed. Based on the results of this study, we suggest the application of a holistic approach to the legislation on hate crimes. This would enable individual redress for the racism to which Sami and Roma, among others, are exposed.